Penegakan Hukum Terhadap Peredaran Kosmetik Ilegal Melalui Media Sosial di Gorontalo - Piloto, Ainun; U. Puluhulawa, Fenty; Apripari (YUDHISTIRA : Jurnal Yurisprudensi, Hukum dan Peradilan, 2025)
The rampant circulation of illegal cosmetics through social media, which is difficult to monitor, poses a serious challenge to consumer protection and the effectiveness of law enforcement in Indonesia. This study aims to analyze the positive legal regulations regarding the sale and purchase of illegal cosmetics via social media and identify factors that hinder law enforcement in Gorontalo City. The phenomenon of the rampant circulation of illegal cosmetics via social media poses a serious challenge, primarily due to the dynamic and difficult-to-monitor nature of digital media. The research method used is an empirical legal approach, with data collection through observation and interviews with Gorontalo BPOM officers and a review of relevant laws and regulations such as the Health Law, the Consumer Protection Law, the ITE Law, and BPOM Regulation No. 18 of 2015. The results of the study indicate that although regulations are available, implementation in the field still faces various obstacles such as a weak deterrent effect, limited human resources and technology, and low public awareness. The conclusion of this study emphasizes the importance of regulatory reform, strengthening the digital capacity of regulatory agencies, and cross-sector collaboration to create more effective legal protection for consumers in the era of digital commerce.